KEPEMIMPINAN TRANSFORMASIONAL DALAM LEMBAGA PENDIDIKAN MADRASAH - Chaerul Rofiq (IAIN Purwokerto, 2019)
The transformation of its essence is to change the potential into real energy. The head of the madrassa who is able to do leadership transformation means can transform the potential of the institution into energy to improve the quality of process and output of education. The implementation of transformational leadership in educational institutions of madrasah refers to how the head of the madrasah can develop a superior culture (the culture of exellence) in madrasah. The head of the madrasah should emphasize the importance of building a culture that contributes to the improvement of the quality of the educational process in schools. The steps that need to be done such as, understand the culture of madrasah community, madrasah understand the values of excellence, elements of culture, quality, build cultural change according to the demands of the community. In this condition, then the leadership that is needed in building the culture of the organization is the leadership which includes the ability of the technical, human, and educational.